Courses
Courses for Kids
Free study material
Offline Centres
More
Store

# If $f\left( x \right) = \left\{ {\dfrac{{{x^2} + \propto }}{{2\sqrt {{x^2} + 1 + B} }}} \right\}$ ${\text{for}}\;x \geqslant 0 \\ {\text{for}}\;x < 0 \\$And $f\left( {\dfrac{1}{2}} \right) = 2$ is continuous at x =0, value of $\left( { \propto ,P} \right)$ is :A) $\left(\dfrac{7}{4}, -\dfrac{1}{4}\right)$B) $\left(4-\sqrt{5},2-\sqrt{5}\right)$C) $\left(0, -1\right)$D) $\left(\dfrac{7}{4}, \dfrac{1}{4}\right)$

Last updated date: 13th Jun 2024
Total views: 412.8k
Views today: 7.12k
Verified
412.8k+ views
Hint: The function to be continuous at a particular point like say a, then we have a condition for a, where $f\left( x \right)$ function needs to have its left hand limit, Right hand limit and value equal to each other. Like $\Rightarrow \dfrac{{\lim }}{{x \to {a^ - }}}\;f\left( x \right) = f\left( a \right) = \;\dfrac{{\lim }}{{x \to {a^ + }}}f\left( x \right)$

Complete step by step solution: let’s begin with the given function which is represented as
$\begin{gathered} f\left( x \right) = \left\{ {\dfrac{{{x^2} + \propto }}{{2\sqrt {{x^2} + 1 + B} }}} \right\}\;\;\;\;\;\;\;\; \\ \\ \end{gathered}$ $\begin{gathered} x \geqslant 0 \\ x < 0 \\ \end{gathered}$
As we know that from given data,$f\left( {{\raise0.5ex\hbox{$\scriptstyle 1$} \kern-0.1em/\kern-0.15em \lower0.25ex\hbox{$\scriptstyle 2$}}} \right) = 2,$ so for this we will use the function $f\left( x \right) = {x^2} + \propto$ because ${\raise0.5ex\hbox{$\scriptstyle 1$} \kern-0.1em/\kern-0.15em \lower0.25ex\hbox{$\scriptstyle 2$}}$ is greater than 0
So, $f\left( {\dfrac{1}{2}} \right) = \dfrac{1}{4} + \propto = 2$
$\Rightarrow \; \propto \; = 2 - \dfrac{1}{4} = \dfrac{7}{4}$
Now we need to find the value of B, and the other information given is they are continuous at x = 0 for being continuous of a function the left hand limit, Right hand limit should be equal.
$so\dfrac{{\;\lim }}{{x \to {0^ - }}}f\left( x \right) = \dfrac{{\lim }}{{x \to {0^ + }}}f\left( x \right)$
$\Rightarrow \dfrac{{\lim }}{{x \to {0^ - }}}\;\left( {{x^2} + \propto } \right) = \dfrac{{\lim }}{{x \to {0^ + }}}2\sqrt {{x^2} + 1} + B)$
$\Rightarrow \lim {\left( 0 \right)^2} + \propto \; = 2\sqrt {{0^2} + } 1 + B$
$\propto - 2 + B$
So we get,$B = \; \propto - 2\;and \propto = {\raise0.5ex\hbox{$\scriptstyle 7$} \kern-0.1em/\kern-0.15em \lower0.25ex\hbox{$\scriptstyle 4$}}$
$\Rightarrow$ we get $B = \; \propto - 2 = \dfrac{7}{4} - 2 = - \dfrac{1}{4}$
Hence we get the value of $\left( { \propto ,B} \right) = \left( {{\raise0.5ex\hbox{\scriptstyle 7} \kern-0.1em/\kern-0.15em \lower0.25ex\hbox{\scriptstyle {4,}}}{\raise0.5ex\hbox{\scriptstyle { - 1}} \kern-0.1em/\kern-0.15em \lower0.25ex\hbox{\scriptstyle 4}}} \right)$ option A is the correct answer.

Note: we know that function to get continuous left-hand limit, Right hand limit and function value should be equal.
$\dfrac{{\lim }}{{x \to {a^ - }}}f\left( x \right) = f\left( a \right) = \dfrac{{\lim }}{{x \to {a^ + }}}f\left( x \right)$ Similarly, for differentiability of a function at point a is checked by
$\dfrac{{\lim }}{{x \to {a^ - }}}f\left( x \right) = f'\left( a \right) = \dfrac{{\lim }}{{x \to {a^ + }}}f'\left( x \right)$